Academic medicine’s glass ceiling: Author’s gender in top three medical research journals impacts probability of future publication success - John E. Krstacic; Brendan M. Carr; Ashutosh R. Yaligar; Annet S. Kuruvilla; Joshua S. Helali; Jamie Saragossi; Chencan Zhu; Robert Hutnik; Mohammad Noubani; Jie Yang; Henry J. Tannous; A. Laurie W. Shroyer (PLoS ONE, 2022)
Introduction In December 2017, Lancet called for gender inequality investigations. Holding other factors constant, trends over time for significant author (i.e., first, second, last or any of these authors) publications were examined for the three highest-impact medical research journals (i.e., New England Journal of Medicine [NEJM], Journal of the American Medical Association [JAMA], and Lancet). Materials and methods Using randomly sampled 2002-2019 MEDLINE original publications (n = 1,080; 20/year/journal), significant author-based and publication-based characteristics were extracted. Gender assignment used internet-based biographies, pronouns, first names, and photographs. Adjusting for author-specific characteristics and multiple publications per author, generalized estimating equations tested for first, second, and last significant author gender disparities. Results Compared to 37.23% of 2002 – 2019 U.S. medical school full-time faculty that were women, women’s first author publication rates (26.82% overall, 15.83% NEJM, 29.38% Lancet, and 35.39% JAMA; all p < 0.0001) were lower. No improvements over time occurred in women first authorship rates. Women first authors had lower Web of Science citation counts and co-authors/collaborating author counts, less frequently held M.D. or multiple doctoral-level degrees, less commonly published clinical trials or cardiovascular-related projects, but more commonly were North American-based and studied North American-based patients (all p < 0.05). Women second and last authors were similarly underrepresented. Compared to men, women first authors had lower multiple publication rates in these top journals (p < 0.001). Same gender first/last authors resulted in higher multiple publication rates within these top three journals (p < 0.001). Discussion Since 2002, this authorship “gender disparity chasm” has been tolerated across all these top medical research journals. Despite Lancet’s 2017 call to arms, furthermore, the author-based gender disparities have not changed for these top medical research journals - even in recent times. Co-author gender alignment may reduce future gender inequities, but this promising strategy requires further investigation.